2014
DOI: 10.3389/fonc.2014.00131
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of Angiogenesis by Immune Cells

Abstract: It is widely accepted that the tumor microenvironment (TUMIC) plays a major role in cancer and is indispensable for tumor progression. The TUMIC involves many “players” going well beyond the malignant-transformed cells, including stromal, immune, and endothelial cells (ECs). The non-malignant cells can acquire tumor-promoting functions during carcinogenesis. In particular, these cells can “orchestrate” the “symphony” of the angiogenic switch, permitting the creation of new blood vessels that allows rapid expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 225 publications
(255 reference statements)
2
101
0
3
Order By: Relevance
“…It was reported that monocytes/macrophages are the most abundant inflammatory cell types of innate immunity in coronary atherothrombosis co-expressing Toll-like receptor 4 [45]. Immune cells, including Tregs, macrophages, monocytes and dendritic cells, have been shown to regulate angiogenesis in different disease settings by providing pro-angiogenic C/Cs and pro-angiogenic niches [64]. However, other roles of thrombus leukocytes, outside of the several reported roles such as triggering thrombosis, causing unstable angina and myocardial infarction, remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that monocytes/macrophages are the most abundant inflammatory cell types of innate immunity in coronary atherothrombosis co-expressing Toll-like receptor 4 [45]. Immune cells, including Tregs, macrophages, monocytes and dendritic cells, have been shown to regulate angiogenesis in different disease settings by providing pro-angiogenic C/Cs and pro-angiogenic niches [64]. However, other roles of thrombus leukocytes, outside of the several reported roles such as triggering thrombosis, causing unstable angina and myocardial infarction, remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation acts as a relevant orchestrator in their insurgence, development, and progression [1, 2, 6, 10]. Inflammatory cells, which comprise cells from innate ad adaptive immunity, are characterized by different phenotype and functions, which involve direct (by contact) or distant (by soluble factors) interaction with their target cells [1214]. Immune cells, form either innate or adaptive immunity, given their cellular plasticity, have been reported to acquire an altered phenotype upon different stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells can also serve as the source of VEGF signaling in organ injury (reviewed by Bruno et al, 2014). We used Tg(lyz:GFP) (Hall et al, 2007) and Tg(mpeg1:YFP) (Roca and Ramakrishnan, 2013) transgenic fish to visualize neutrophils and macrophages, respectively, after acute ethanol exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Immune cells have been shown to participate in VEGF signaling in organ injury (reviewed by Bruno et al, 2014). They can directly contribute to alcoholic steatosis, angiogenesis and fibrogenesis by producing pro-inflammatory cytokines such as IL-1β and IL-6 (reviewed by Seo and Jeong, 2016).…”
Section: Discussionmentioning
confidence: 99%